SYSTEMATIC LITERATURE REVIEW : FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI CABAI - Mellinia, Salwa Putri; Wakhidati, Yusmi Nur; Sri Lestari; Imam Widhiono M.Z; Budi Dharmawan (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
The analysis of factors affecting chili production aims to determine the factors that can affect chili production. This study aims to 1) find out the method applied in determining respondents, 2) find out the method applied to collect data on chilli production factors, and 3) find out what factors can affect chilli production. The method applied in this research is a literature review of the factors that influence chili production. The literature sources used include books, scientific journals, and reliable sources. The results show that 1) the highest frequency in the method of determining respondents is simple random sampling; 2) the highest frequency in the category of data collection methods is done using questionnaires and interviews (96 respondents); and 3) the category of the most dominant factors affecting chili production is land area, seed use, and labor.